Microbiological Evaluation of Garlic Extract and SwissADME Profiling of Allicin as an Antimicrobial Candidate - Errol Rakhmad Noordam; Kusno Haryanto; Iin Hardiyati Iin Hardiyati; Anjas Wilapangga; Dian Yudianto; Dede Komarudin; Pristiyantoro Pristiyantoro (Jurusan Farmasi Universitas Negeri Gorontalo, 2026)
This study aimed to evaluate the microbiological quality of garlic extract using a rapid ready-to-use plate system (Easy Plate) and to assess the physicochemical and pharmacokinetic properties of allicin through in silico analysis using SwissADME. Microbiological testing was performed on garlic extract samples targeting coliforms, Staphylococcus aureus, and Enterobacteriaceae. The in silico analysis evaluated physicochemical characteristics, solubility, pharmacokinetic properties, and drug-likeness parameters of allicin. The microbiological results showed no detectable bacterial growth in the tested garlic extract samples under the applied conditions. SwissADME analysis indicated that allicin has favorable properties, including compliance with Lipinski’s Rule of Five, balanced lipophilicity, good predicted water solubility, and high gastrointestinal absorption. These findings suggest that garlic extract exhibited acceptable microbiological quality under the present test conditions, while allicin demonstrated promising drug-like characteristics as a bioactive organosulfur compound. However, the microbiological findings should be interpreted cautiously because the intrinsic antimicrobial activity of garlic extract may affect microbial recovery, and the in silico results remain predictive and require further experimental validation.